Using a mobility assistance dog reduces upper limb effort during manual wheelchair ramp ascent in an individual with spinal cord injury - Gagnon, Dany (Maney Publishing, 2013)
OBJECTIVE: To compare the mechanical and muscular efforts generated in the non-dominant upper limb (U/L) when ascending a ramp with and without the use of a mobility assistance dog (AD(Mob)) in a manual wheelchair user with a spinal cord injury. METHOD: The participant ascended a ramp at natural speed using his personal wheelchair with (three trials) and without (three trials) his AD(Mob). Movement parameters of the wheelchair, head, trunk, and non-dominant U/L (i.e. hand, forearm, and arm segments) were recorded with a motion analysis system. The orthogonal force components applied on the hand rims by the U/Ls were computed with instrumented wheels. Muscular activity data of the clavicular fibers of the pectoralis major, the anterior fibers of the deltoid, the long head of the biceps brachii, and the long head of the triceps brachii were collected at the non-dominant U/L. RESULTS: During uphill propulsion with the AD(Mob), the total and tangential forces applied at the non-dominant handrim, along with the rate of rise of force, were reduced while mechanical efficiency was improved compared to uphill propulsion without the AD(Mob). Similarly, the resultant net joint movements (wrist, elbow, and shoulder) and the relative muscular demands (biceps, triceps, anterior deltoid, pectoralis major) decreased during uphill propulsion with an AD(Mob) versus without an AD(Mob). CONCLUSION: Propelling uphill with the assistance of an AD(Mob) reduces U/L efforts and improves efficiency compared to propelling uphill without its assistance in a manual wheelchair user with a spinal cord injury.